Organizational commitment, job satisfaction and their possible influences on intent to turnover - Ramalho Luz, Carolina Machado Dias; Luiz de Paula, Sílvio; de Oliveira, Lúcia Maria Barbosa (Revista de gestão, 2018)
Purpose The purpose of this paper is to investigate the extent to which the organizational commitment and job satisfaction influence intent to turnover. Design/methodology/approach Following a quantitative approach regarding methodological aspects of this research, a case study was carried out in a company of information technology and communication located in Porto Digital, in the Northeast of Brazil. A data collection technique with 172 forms, a self-administered form with 18 closed questions with a Likert-type scale and an open questionnaire were used. In this analysis, Statistical Package for the Social Sciences (SPSS) software was used as the technique; besides the descriptive statistics, a correlation was made between dependent variables (intention of rotation) and independent variables (affective, normative, instrumental and work satisfaction). The level of organizational commitment in its three dimensions (affective, normative and instrumental), the job satisfaction in its five dimensions (satisfaction with nature of the task, with leadership, with colleagues, with salary and promotions) and the level of intent to turnover from the respondents were investigated. Findings The results suggest that affective and normative commitments and satisfaction with pay, satisfaction with promotions and satisfaction with the nature of the work are correlated with the intention of negative turnover significantly. Among the demographic factors, only the age showed a negative correlation with intent to turnover. By performing multiple regression analysis, we identified that the variables that most impacted the turnover intention are affective commitment, satisfaction with salary and normative commitment. The qualitative portion of this study was accomplished through a content analysis of the open question of the form. Finally, one of the main considerations is the findings that revealed variables other than those adopted in the study, which influence the permanence of the respondents. Research limitations/implications Among the limitations of the research a single case study is highlighted that replicates the experience in other ICT companies to verify if the results found are similar in other organizations and in other segments. The findings direct the construction and validation of new scales, the creation of qualitative protocols to identify the variables that influence the retention of a specific group of individuals to serve as a guide for the elaboration of a questionnaire, as well as creation of surveys of longitudinal nature to correlate the data of intention of rotation with the effective turnover. Practical implications Based on the results, organizations can reduce voluntary evasion by adjusting actions, policies and practices, directing those responsible for People Management to attract and retain good employees. It should be emphasized that voluntary turnover should be treated as one of the management indicators of greater relevance by organizations, representing a thermometer of all human capital management. Social implications The monitoring of employment and unemployment levels is part of the public policy agenda for generating employment and income in Brazil. For organizations, employee turnover can and should be managed and monitored so that appropriate levels are found and their consequences are minimized through effective solutions. The results are important both for technology-based organizations and for all stakeholders interested in the subject as the public power. Originality/value Although in the international literature turnover is a topic of study for many years, in the Brazilian context, there is a shortage of research on the subject, specifically in the sector of advanced technology where there is a great lack of skilled labor, a fierce competition and where to keep employees standard high becomes a survival factor. This study may contribute to the exploration in the local literature, as it will help locate the academy on the Brazilian reality and open the doors to new research works on turnover and its possible correlations with other variables besides organizational commitment and job satisfaction.